2017
DOI: 10.1111/jce.13193
|View full text |Cite
|
Sign up to set email alerts
|

Focal Transcatheter Cryoablation: Is a Four‐Minute Application Still Required?

Abstract: Single 2-minute and 4-minute application times result in catheter ablation lesions of similar size using the modern cryoablation system with nitrous oxide as a refrigerant. While these findings suggest the potential to reduce the standard 4-minute application time, further studies are required to compare clinical efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Five observational studies provided data on the short‐ to midterm outcome in patients after PVI using CB‐Adv for the treatment of persistent AF, being in line with published data after RF ablation . Interest in using CB‐Adv for PVI is increasing, because procedure times are shorter with CB ablation than with RF ablation, due to reduced freeze cycle times and single‐shot applications, not being associated with smaller lesion surface areas using nitrous oxide as refrigerant …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Five observational studies provided data on the short‐ to midterm outcome in patients after PVI using CB‐Adv for the treatment of persistent AF, being in line with published data after RF ablation . Interest in using CB‐Adv for PVI is increasing, because procedure times are shorter with CB ablation than with RF ablation, due to reduced freeze cycle times and single‐shot applications, not being associated with smaller lesion surface areas using nitrous oxide as refrigerant …”
Section: Discussionsupporting
confidence: 54%
“…Five observational studies 6-10 provided data on the short-to midterm Interest in using CB-Adv for PVI is increasing, because procedure times are shorter with CB ablation than with RF ablation, 15,16 due to reduced freeze cycle times 17 and single-shot applications, 18,19 not being associated with smaller lesion surface areas using nitrous oxide as refrigerant. 20 Furthermore, there is some evidence, that PVI alone is not inferior to additional substrate modification in patients with paroxysmal AF, as well as in patients with persistent AF. 21 Interestingly, the success rate for PVI alone in the STAR-AF trial 21 was higher than previously reported.…”
Section: Three-year Outcomementioning
confidence: 99%
“…This is in agreement with a recently published paper exploring the difference in lesion size when varying the freeze time of cryoablation. 12 In the past, the recommended dosage for cryoablation has been 2 freeze cycles of 4 min each; more recent studies have sought to titrate the time needed for ablation to minimalize collateral damage that comes with longer freeze cycles. 8,13,14 The data presented here show that for PVI, 1 freeze cycle of 3 min is sufficient to create permanent scar.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why we did not perform epicardial cryoablation is that inserting the cryocatheter deep inside the CS via a femoral access in all cases seemed to be technically challenging due to the large catheter size (9 Fr) and less maneuverability of the cryocatheter as compared with the RF catheters based on our initial experience. We used a 2‐minute freeze dose to create linear block as single 2‐ and 4‐minute application times have resulted in catheter ablation lesions of a similar size using the modern cryoablation system in an experimental study 13 …”
Section: Discussionmentioning
confidence: 99%